Has the frequency of bleeding changed over time for patients presenting with an acute coronary syndrome? The Global Registry of Acute Coronary Events - Fox, Keith A.A. (Oxford University Press, 2010)
AIMS: To determine whether changes in practice, over time, are associated with altered rates of major bleeding in acute coronary syndromes (ACS). METHODS AND RESULTS: Patients from the Global Registry of Acute Coronary Events were enrolled between 2000 and 2007. The main outcome measures were frequency of major bleeding, including haemorrhagic stroke, over time, after adjustment for patient characteristics, and impact of major bleeding on death and myocardial infarction. Of the 50 947 patients, 2.3% sustained a major bleed; almost half of these presented with ST-elevation ACS (44%, 513). Despite changes in antithrombotic therapy (increasing use of low molecular weight heparin, P < 0.0001), thienopyridines (P < 0.0001), and percutaneous coronary interventions (P < 0.0001), frequency of major bleeding for all ACS patients decreased (2.6 to 1.8%; P < 0.0001). Most decline was seen in ST-elevation ACS (2.9 to 2.1%, P = 0.02). The overall decline remained after adjustment for patient characteristics and treatments (P = 0.002, hazard ratio 0.94 per year, 95% confidence interval 0.91–0.98). Hospital characteristics were an independent predictor of bleeding (P < 0.0001). Patients who experienced major bleeding were at increased risk of death within 30 days from admission, even after adjustment for baseline variables. CONCLUSION: Despite increasing use of more intensive therapies, there was a decline in the rate of major bleeding associated with changes in clinical practice. However, individual hospital characteristics remain an important determinant of the frequency of major bleeding.